Charles Dickens et le « nouveau pittoresque » - Nathalie Vanfasse (Cahiers Victoriens et Edouardiens)
The picturesque is an aesthetic ideal which became almost a cult between the end of the eighteenth century and the beginning of the nineteenth century. Its success can be explained by the fact that it appealed to all classes of society and did not require any extensive artistic knowledge to be appreciated and commented upon. Through its taste for wild and irregular nature, the picturesque broke with classicism. However it did not include the exaltation of romanticism. In this respect it can be considered as a feature of pre-romanticism. For the Victorians it remained a reference in the field of representation, though some people questioned its approach. The critic Alexander M. Ross has stressed the impact of the picturesque on novels of that period. The word « picturesque » appears frequently in Dickens’s novels. This paper will show however that the novelist used it in a broader sense than its strict definition by its theoreticians William Gilpin, Sir Uvedale Price and Richard Payne Knight, and that he even redefined the notion to pave the way for the conception of a « new picturesque. »